2010
DOI: 10.1097/ana.0b013e3181de4eae
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Motor-evoked Potentials on Cerebral Aneurysm Surgery and New-onset Postoperative Motor Deficits

Abstract: Surgical clipping may cause stenosis of parent arteries or occlusion of perforating arteries in cerebral aneurysm surgery. To prevent postoperative motor deficits, motor-evoked potentials (MEPs) have been used. This enables to detect cerebral ischemia. However, the rate of false negatives (motor deficits with preserved MEP) has been relatively higher than in aortic surgery. We hypothesized that postoperative motor deficits with preserved intraoperative MEP do not always represent false negatives. We reviewed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…These results suggest that clip rotation or other causes of a delayed ischemic event can occur in MCA aneurysmal surgery, and they cannot be detected during the operation [10,20]. SSEP is known to help detect parenchymal injury and to reduce postoperative complication.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results suggest that clip rotation or other causes of a delayed ischemic event can occur in MCA aneurysmal surgery, and they cannot be detected during the operation [10,20]. SSEP is known to help detect parenchymal injury and to reduce postoperative complication.…”
Section: Discussionmentioning
confidence: 88%
“…reported that 40 % of the patients with no changes in MEP during surgery showed a delayed motor deficit [10]. These results suggest that clip rotation or other causes of a delayed ischemic event can occur in MCA aneurysmal surgery, and they cannot be detected during the operation [10,20].…”
Section: Discussionmentioning
confidence: 97%
“…More recently, other investigators have had better success rates with transcranial MEP monitoring during intracranial aneurysm clipping, but they have used very high stimulus intensity with a continuous infusion of muscle relaxant for partial neuromuscular blockade, or they have monitored only upper extremities (10,18,31). The use of muscle relaxant in these patients has several drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of these studies met the inclusion criteria ( Fig. 1) 11,12,14,15,24,26,[35][36][37][38][39][41][42][43] . They include 1597 patients (95% CI: 276, 2881) with a total of 1689 (336, 3042) aneurysms; 1556 (92.0%) aneurysms in the anterior circulation and 134 (8.0%) in the posterior circulation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%